Mixed Methods Research: An Overview - pandey Bista, Archana; Shrama, Muna (Journal of Nursing Education of Nepal, 2023)
The mixed methods research employs rigorous quantitative research assessing magnitude and frequency of constructs and rigorous qualitative research exploring the meaning and understanding of constructs. The design utilizes multiple methods and integrating these methods to draw on the strengths of each and framing the investigation within philosophical and theoretical positions. Mixed methods studies provide opportunities for combination of a variety of theoretical perspectives with multiple purposes. The basic concept is that integration of quantitative and qualitative data maximizes the strengths of each type of data. Generally,three approaches are used to integrate namely, merging data; connecting data; and embedding data. In nursing practice, usually, four types of mixed methods designs are used. These are convergent parallel design, sequential explanatory design, and sequential exploratory design and embedded design
Keywords: NA